The Influence of Underwriter Reputation and Firm Age on IPO Pricing Decision: A Study on Companies Conducting IPOs on the Indonesia Stock Exchange in 2021–2024 - Nathan, Daniel; Sari, Prima Yusi (Universitas Padjadjaran, 2025)
This study aims to analyze the effect of underwriter’s reputation and firm age on IPO pricing decision among companies that went public on the Indonesia Stock Exchange (IDX) during the period 2021 to 2024. A quantitative approach was employed using multiple linear regression to examine the relationships between variables. The study’s sample consists of 229 companies that conducted IPOs within the specified period. The independent variables include underwriter’s reputation, categorized based on transaction volume rankings, and firm age, calculated as the difference between the year of establishment and the IPO year. The dependent variable is IPO pricing decision, represented by the natural logarithm of the offer price. Classical assumption tests and regression analyses were conducted to identify statistically significant influences. The results show that underwriter’s reputation has a positive and significant effect on IPO pricing decision, highlighting the importance of third-party credibility in reducing uncertainty and signaling firm quality to investors. In addition, firm age also has a positive and significant influence, indicating that older firms tend to be perceived as more stable and less risky. Meanwhile, the control variable, institutional ownership, does not show a significant impact. These findings are supported by the results of a difference test, which confirms a significant pricing disparity between companies employing reputable underwriters and those that do not.